Oxygen Therapy Lowers Right Ventricular Afterload in Experimental Acute Pulmonary Embolism. Issue 9 (September 2021) - Lyhne, Mads Dam; Hansen, Jacob Valentin; Dragsbæk, Simone Juel; Mortensen, Christian Schmidt; Nielsen-Kudsk, Jens Erik; Andersen, Asger
Abstract : OBJECTIVES: To investigate if oxygen could unload the right ventricle and improve right ventricle function in a porcine model mimicking intermediate-high risk acute pulmonary embolism. DESIGN: Controlled, blinded, animal study. SETTING: Tertiary university hospital, animal research laboratory. SUBJECTS: Female, Danish pigs ( n = 16, approximately 60 kg). INTERVENTIONS: Acute autologous pulmonary embolism was induced until doubling of baseline mean pulmonary arterial pressure. Group 1 animals ( n = 8) received increasing FIO2 (40%, 60%, and 100%) for time intervals of 15 minutes returning to atmospheric air between each level of FIO2 . In group 2 ( n = 8), the effects of FIO2 40% maintained over 75 minutes were studied. In both groups, pulmonary vasodilatation from inhaled nitric oxide (40 parts per million) was used as a positive control. MEASUREMENTS AND MAIN RESULTS: Effects were evaluated by biventricular pressure-volume loop recordings, right heart catheterization, and arterial and mixed venous blood gasses. Pulmonary embolism increased mean pulmonary arterial pressure from 15 ± 4 to 33 ± 6 mm Hg ( p = 0.0002) and caused right ventricle dysfunction ( p < 0.05) with troponin release ( p < 0.0001). In group 1, increasing FIO2 lowered mean pulmonary arterial pressure ( p < 0.0001) and pulmonary vascular resistance ( p = 0.0056) and decreased right ventricle volumes ( p = 0.0018) and right ventricle mechanical work ( p = 0.034). Oxygenation was improved and pulmonary shunt was lowered ( p < 0.0001). Maximal hemodynamic effects were seen at FIO2 40% with no additional benefit from higher fractions of oxygen. In group 2, the effects of FIO2 40% were persistent over 75 minutes. Supplemental oxygen showed the same pulmonary vasodilator efficacy as inhaled nitric oxide (40 parts per million). No adverse effects were observed. CONCLUSIONS: In a porcine model mimicking intermediate-high risk pulmonary embolism, oxygen therapy reduced right ventricle afterload and lowered right ventricle mechanical work. The effects were immediately present and persistent and were similar to inhaled nitric oxide. The intervention is easy and safe. The study motivates extended clinical evaluation of supplemental oxygen in acute pulmonary embolism. Abstract : Supplemental Digital Content is available in the text.